The Impact of Animation Program on Arabic Learning Vocabulary Recall Among Primary School Pupels: A Case Study at Al-Amin Islamic Primary School, Gombak - Ahmed Mohamed, Ismaiel Hassanein; Mokhtar, Mahani (2019)
In Al Amin Gombak Islamic Primary School, vocabulary recall and acquisition of verbal skills is a major concern in Arabic Language Learning. Classical teaching techniques and learning materials has become ineffective in ensuring the acquisition of those skills. Although each class is equipped with a HD television that can be connected to a laptop via a USB cable, animation programs have yet to be used by the teachers in teaching Arabic Language.